THE EFFECT OF FINANCIAL LITERACY AND INCLUSION ON THE LEVEL OF BUSINESS RESILIENCE IN SMES IN TASIKMALAYA - Lili Latipah; Azizah Fauziyah; Ismail Yusup (Jurnal Ekonomi, 2023)
Tasikmalaya is one of the cities with high potential for Small and medium-sized enterprises (SMEs). Barriers that occur in SMEs today make the resilience of SMEs in Tasikmalaya City face problems in various aspects. It causes SMEs that cannot last long or their business continues. SMEs require strategic efforts to maintain business continuity. One of its efforts is to increase the literacy of financially literate SMEs actors . The purpose of this study is to illustrate the impact of financial literacy and inclusion on the level of business resilience in Tasikmalaya city. The sample from this study was 96 SMEs from 811 SMEs population who already have business licenses in Tasikmalaya City. Findings from this study show that financial literacy and inclusion simultaneously impact organizational resilience, with an R-square of 0.861 or 86%. It means that financial literacy and inclusion affect business resilience in Tasikmalaya by 86%. This research is expected to be a recommendation for SMEs to enrich literacy with their financial knowledge. In addition, support from the government or parties related to regulation, education and facilitation is expected to encourage SMEs in Tasikmalaya City to become capital in maintaining their business.